Level of Evidence of Abstract Presentations at Brazilian Plastic Surgery Annual Meetings - Denadai, Rafael; Pinho, Andre S; Junior, Hugo S; Denadai, Rodrigo; Raposo-Amaral, Cassio Eduardo (The Journal of craniofacial surgery, 2016)
The purposes of this study were to assess trends in the level of evidence of the abstracts presented at a major Brazilian plastic surgery annual meeting, and evaluate the factors associated with a higher level of evidence. Abstracts (n = 400) presented at the 2010 to 2013 Brazilian Congresses of Plastic Surgery were analyzed for level of evidence (levels I-V). All abstracts were also classified into a higher (levels I and II) or lower (levels III, IV, and V) level of evidence. Bivariate and multivariate analyses were applied to evaluate the possible determinants (year, period, number of authors, number of subjects, plastic surgery topic, and presence of statistical analysis) of higher level of evidence. The weighted average level of evidence was 3.39, with a significant (all P <0.05) overall predominance in the proportion of level of evidence III and lower level of evidence. There was a significant (all P <0.05) increase in the proportion of level of evidence II and higher level of evidence in the evaluated years and periods. Bivariate and multivariate analyses revealed that the year 2013, period 2012 to 2013, ≥6 authors/abstracts, and presence of statistical analysis to be the most significant (all P <0.05) predictive factors of higher level of evidence. Brazilian plastic surgery meeting abstracts demonstrated an overall predominance of lower level of evidence and a trend to increase the higher level of evidence, whereas the year 2013, period 2012 to 2013, ≥6 authors/abstracts, and the presence of statistical analysis were determinants of higher level of evidence.